EVALUATION OF RIGOR MORTIS AS AN INDICATOR OF ESTIMATED TIME OF DEATH: A SYSTEMATIC REVIEW - Lestari, Wulan Suci; Maulina, Nora (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Estimating time of death is an important aspect of forensic investigations, with rigor mortis as one of the main indicators used. This study aimed to evaluate the role of rigor mortis in determining the post-mortem interval (PMI) based on a systematic review of recent literature from 2020 to 2025. A total of 30 articles were identified, with 10 articles meeting the eligibility criteria. The analysis showed that rigor mortis begins to develop within 1-4 hours after death, reaches its peak within 6-12 hours, and disappears after 36-72 hours. Environmental factors, such as temperature and humidity, had a significant effect on the speed of rigor mortis development. In addition, physiological conditions before death also contribute to variations in the onset and duration of rigor mortis. These findings emphasize the importance of considering environmental and biological factors in estimating time of death to improve the accuracy of forensic analysis